Insect world. - Time-Life Books (Alexandria, Va. : Time-Life Books, 1988)
Presents, in question and answer format, information about the behavior, food-gathering, defenses, anatomy, and surprising habits of all kinds of insects.
3.6
3-6
Keywords: Insects -- Miscellanea -- Juvenile literature; Insects -- Miscellanea; Questions and answers; Insects -- Miscellanea; Questions and answers